Analyse des inégalités de revenu au Mali - Paul Alkemade; Daniele Checchi; Siaka Cissé; Aminata Coulibaly; Anda David; Amadou Koné; Teresa Munzi; Gaston Sodio; Arouna Sougane (Luxembourg Income Study (LIS), 2021)
– In discussions on inequality in Africa, Mali often appears as an exception, being the country with the lowest level of inequality in the West African sub-region. In this paper, we analyse the dynamics of inequality in the country and try to understand the role played by the different sources of income. To do so, we use the LIS harmonized version of the 3 waves of the Modular and Permanent Household Survey (MPHS) and our results show an increase in inequality in 2019. Furthermore, we find that income inequalities are mainly due to the duality of the labour market, which then reinforces spatial inequalities. Given the prevalence of the informal sector and the very limited existence of social safety nets, social protection does not play its role in reducing inequalities.
Keywords: 330; Einkommensverteilung; Vermögensverteilung; Mali